Higher spin analogs of linearized topologically massive gravity and linearized new massive gravity - Dalmazi, D. [UNESP]; Dos Santos, A. L.R. (American Physical Society (APS), 2021)
We suggest a new spin-4 self-dual model (parity singlet) and a new spin-4 parity doublet in D=2+1. They are of higher order in derivatives and are described by a totally symmetric rank-4 tensor without extra auxiliary fields. Despite the higher derivatives they are ghost free. We find gauge invariant field combinations which allow us to show that the canonical structure of the spin-4 (spin-3) models follows the same pattern of its spin-2 (spin-1) counterpart after field redefinitions. For s=1, 2, 3, 4, the spin-s self-dual models of order 2s-1 and the doublet models of order 2s can be written in terms of three gauge invariants. The cases s=3 and s=4 suggest a restricted conformal higher spin symmetry as a principle for defining linearized topologically massive gravity and linearized new massive gravityfor arbitrary integer spins. A key role in our approach is played by the fact that the Cotton tensor in D=2+1 has only two independent components for any integer spin.